Rallying around the EU Flag: Russia's Invasion of Ukraine and Attitudes toward European Integration - Nils Steiner; Ruxanda Berlinschi; Etienne Farvaque; Jan Fidrmuc; Philipp Harms; Alexander Mihailov; Michael Neugart; Piotr Stanek (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper uses a survey among students at European universities to explore whether Russia's invasion of Ukraine has affected attitudes toward European integration. Some respondents completed the survey just before Russia's assault on February 24, 2022, and some did so just afterwards, thus delivering a quasi-experimental design situation, which we exploit. Our results suggest that the ominous news about the Russian attack increased the participants' interest in EU politics, consolidated their attachment to the EU, and made them more mindful and appreciative of the benefits of deeper European integration. In effect, the war so close to the EU Eastern border provoked a rally around the supranational EU flag, with convergence of public opinion toward shared European values.
Keywords: F02; F50; H77; N44; Z18; 330; European integration; EU attitudes; external threat; rally around the flag; Ukraine; Russia